Effect of tillage management on the wind erosion of arable soil in the Chinese Mollisol region - Chen, Shuai; Zhang, Xingyi; Li, Jianye; Guo, Mingming; Hu, Wei (Frontiers in Environmental Science, 2022)
Wind erosion is a serious problem in agricultural regions and threaten the regional food production in Northeast China. However, limited information is available on the characteristics of wind erosion in arable soil in Northeast China. As a result, field-based research during periods of vulnerability to wind erosion is essential. This study quantified the characteristics of soil wind erosion under no-tillage (NT) and conventional tillage (CT) treatments in China’s northern “corn-belt”. The results determined the wind erosion transport mode of Mollisols to be generally characterized by creep, and supplemented by saltation and suspension in Northeast China. The erodible particles of the creep accounted for 80.37% and 85.42% of the total wind erosion under the NT and CT treatments, respectively. During the experiments with erodible particles in saltation mode from the soil surface to 2 m, the majority of the particles were collected by the sampler at 0.5 m height, with the NT and CT treatments collecting 5.82 kg·m-2 and 6.93 kg·m-2 of erodible particles per unit area, respectively. The wind erosion on agricultural land was observed to be influenced by tillage practices, rainfall, wind speed and soil moisture content. Average and maximum wind speed exhibited significant positive correlations with wind erosion during April and May. Moreover, the erodible particles of each wind erosion transport mode (creep, saltation and suspension) under CT were higher (1.73, 1.41 and 1.35 times) than those under the NT treatment. With less damage and a greater protection of the surface soil, the NT treatment was able to decrease the occurrence of wind erosion and influence its outcome on farmland. Therefore, the NT treatment should be encouraged as a key initiative for the reduction of the wind erosion of arable soil in the Chinese Mollisol region.